Keterampilan Berpikir Kritis dan Hasil Belajar Siswa dalam Model Pembelajaran Generatif Disertai Media Alat Percobaan Sederhana - Sherly Eka Putri Damayanti; Singgih Bektiarso; Maryani Maryani (Pendidikan Fisika UIN Alauddin Makassar, 2023)
The purpose of this study was to examine the effect of the generative learning model with simple experimental media on critical thinking and student learning outcomes. This research uses true experimental research with post test only control design. Determination of the research sample is done by cluster random sampling. The data collection instrument used was a multiple choice test and a description. Based on the results of critical thinking data analysis using the Independent T-test, Sig. (2-tailed) worth 0.001 where 0.001 is less than 0.05, indicating that the difference in the average critical thinking value of the experimental class students is greater than the control class. Meanwhile, for learning outcomes using the Mann-Whitney test, a value of 0.006 was obtained, where the value was less than 0.05, meaning that the difference in the average value of student learning outcomes in the experimental class was greater than the control class. Significantly the difference between the two shows that the generative learning model with simple experimental media has an effect on critical thinking and student learning outcomes of physics. Key Words : Generative learning model; Simple experimental tool; Critical thinking; Learning outcomes